Profoundly Expanded T-cell Clones in the Inflamed and Uninflamed Intestine of Patients With Crohn's Disease. (2nd February 2017) - Doorenspleet, M. E.; Westera, L.; Peters, C. P.; Hakvoort, T. B. M.; Esveldt, R. E.; Vogels, E.; van Kampen, A. H. C.; Baas, F.; Buskens, C.; Bemelman, W. A.; D'Haens, G.; Ponsioen, C. Y.; et al.
Abstract: Background and Aim: T cells are key players in the chronic intestinal inflammation that characterises Crohn's disease. Here we aim to map the intestinal T-cell receptor [TCR] repertoire in patients with Crohn's disease, using next-generation sequencing technology to examine the clonality of the T-cell compartment in relation to mucosal inflammation and response to therapy. Methods: Biopsies were taken from endoscopically inflamed and uninflamed ileum and colon of 19 patients with Crohn's disease. From this cohort, additional biopsies were taken after 8 weeks of remission induction therapy from eight responders and eight non-responders. Control biopsies from 11 patients without inflammatory bowel disease [IBD] were included. The TCRβ repertoire was analysed by next-generation sequencing of biopsy RNA. Results: Both in Crohn's disease patients and in non-IBD controls, a broad intestinal T-cell repertoire was found, with a considerable part consisting of expanded clones. Clones in Crohn's disease were more expanded [ p = 0.008], with the largest clones representing up to as much as 58% of the total repertoire. There was a substantial overlap of the repertoire between inflamed and uninflamed tissue and between ileum and colon. Following therapy, responders showed larger changes in the T-cell repertoire than non-responders, although a considerable part of the repertoire remained unchanged in both groups. Conclusions: The intestinal T-cell repertoire distribution in Crohn's disease is different from that in the normal gut, containing profoundly expanded T-cell clones that take up a large part of the repertoire. The T-cell repertoire is fairly stable regardless of endoscopic mucosal inflammation or response to therapy.